2009
DOI: 10.1071/bt09043
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive biology, post-fire succession dynamics and population viability analysis of the critically endangered Western Australian shrub Calytrix breviseta subsp. breviseta (Myrtaceae)

Abstract: Calytrix breviseta Lindl. subsp. breviseta is a critically endangered, obligate-seeder shrub within fire-prone kwongan of south-west Western Australia. Little is known about the species’ reproductive biology and how threatening processes, particularly altered fire regimes and exotic species invasion, will impact the long-term viability of the species. This study aims to elucidate the species’ reproductive biology and patterns of seedling recruitment during succession after fire. The effects of changes to the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…In the absence of long-term field data, some scientists have modelled outcomes of various fire regimes on the persistence of plant populations, based on vital attributes and life histories (Bradstock et al 1997;Bradstock et al 1998;Enright et al 1998;Groeneveld et al 2008;Nield et al 2009). While modelling can provide valuable insights, the models necessarily make assumptions about fire behavior and plant responses (Ooi et al 2006;Burrows and Middleton 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of long-term field data, some scientists have modelled outcomes of various fire regimes on the persistence of plant populations, based on vital attributes and life histories (Bradstock et al 1997;Bradstock et al 1998;Enright et al 1998;Groeneveld et al 2008;Nield et al 2009). While modelling can provide valuable insights, the models necessarily make assumptions about fire behavior and plant responses (Ooi et al 2006;Burrows and Middleton 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Mass germination follows heat shock, which seeds would experience during a fire, leading to greater population sizes, replenishment of the soil seed bank and greater resilience to impacts such as grazing. This recruitment strategy has been recognised for other post-fire recruiters [ 52 , 53 ]. Maturation of recruits germinating in the absence of fire may be affected by native and exotic herbivores, or competition from native and exotic plants; these factors may threaten populations persisting where fire has been absent, although this needs further attention.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research in shrublands, mallee-heaths and kwongan provide some support for this proposition with significant correlations between senescence and structural decline with time since fire (Gosper et al., 2012, Gosper et al., 2013). Furthermore, numerous studies have demonstrated that some threatened species are most abundant in the first decade after fire and gradually retreat from the plant community to persist as seeds in the soil until the passage of another fire (Yates and Broadhurst, 2002, Yates et al., 2003, Yates and Ladd, 2005; Nield et al., 2009).…”
Section: Case Studies Illustrating Recovery Of Threatened Speciesmentioning
confidence: 99%